PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KOMITMEN ORGANISASI SERTA DAMPAKNYA TERHADAP KINERJA GURU SMK MUHAMMADIYAH SALATIGA - Samtono Samtono (Among Makarti, STIE AMA Salatiga, 2017)
Abstract The purpose of the research is to examine and analyze the influence of the organizational culture and principle’s leadhership and commitment organizational and its affect on teacher’s performance in SMK Muhammadiyah Salatiga. The research was conducted to high school teacher of SMK Muhammadiyah Salatiga as many as 65 respondents. The data obtained were processed using descriptive analysis and multiple regression analysis to determine the affect of independent variables on the dependent variables. The show that ( 1 ) The organizational culture has positive affect to commitment organizational, ( 2 ) The principle’s leadhership has negative affect to commitment organizational, ( 3 ) The commitment organizational has positive affect to teacher’s performance, ( 4 ) The principle’s leadhership has negative affect to teacher’s performance, ( 5 ) The commitment organizational has positive affect to teacher’s performance, ( 6 ) The influence of organizational culture to the commitment organizational positive affect to teacher’s performance, ( 7 ) The influence of the principle’s leadhership to the commitment organizational positive affect the theachr’s performance. Keywords : The Organizational culture, Principle’s Leadhership, Organizational Commitment, Teacher’s Performance.